PENERAPAN PSAK KONVERGENSI IFRS TERHADAP RELEVANSI NILAI INFORMASI AKUNTANSI DAN ASIMETRI INFORMASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Kuntjoro, Victoria; Lindrawati, Lindrawati (Jurnal Akuntansi Kontemporer, 2017)
IFRS is an accounting standard that emphasizes the use of fair value. The use of fair value is a fulfillment of “relevance” qualitative characteristics, so IFRS can increase the value relevance of accounting information. Value relevance of accounting information is measured using price model and return model. IFRS also requires the “full disclosure”, so that the use of IFRS can reduce the information asymmetry. Currently, IFRS has been converged into PSAK. IAI establish that the convergence of IFRS which refers to IFRS effective January 1, 2009 was implemented on January 1, 2012. Therefore, the aim of this study is to examine and analyze whether the implementation of PSAK-IFRS convergence can improve the value relevance of accounting information and make a difference in information asymmetry. The research design for the value relevance of accounting information is descrip-tive. While for information asymmetry is qualitative with hypothesis. The object of the research is manufacturing companies listed on the Indonesian Stock Exchange in 2010-2013 with a sample of 50 companies selected by purposive sampling technique. Tech-niques of data analysis used are simple linier regression, multiple linier regression, and Wilcoxon test. The results showed that based on price model, the use of PSAK-IFRS convergence can increase the value relevance of accounting information. While based on the return model, the implementation of PSAK-IFRS convergence can not increase the value relevance of accounting infor-mation. The results of this study also showed that there is no information asymmetry difference before and after implementation of PSAK-IFRS convergence.